The Effect of Commissioner Board’s Characteristics, Risk Management Committee, And Auditor's Reputation on The Risk Management Disclosure - D, Sabrina Rizki Febriyanti N; Ghofar, Abdul (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study aims to analyze the effect of commissioner board characteristics, risk management committee, and auditor reputation on risk management disclosure. The samples are selected through purposive sampling technique, resulting in 141 secondary data of the annual reports of consumer goods companies in 2019-2021 analyzed by multiple linear regression and robustness test as the additional test. The results exhibit that commissioner board size and risk management committee have a positive effect on risk management disclosure; commissioner board gender diversity, commissioner board educational background, and auditor reputation have no effect on risk management disclosure. The robustness test reveals consistent results with that of the major test, as such, the study model is robust.